Health-Related Quality of Life of Mothers of Children With Intellectual Disability - Mohammad Lalehgani Dezaki; Gholamreza Ghaedamini Harouni; Sina Ahmadi; Meroe Vameghi; Homeira Sajjadi; Mansoore Ghafari (Iranian Rehabilitation Journal, 2018)
Objectives: Disability occurs as a sudden and unexpected incident, and coping with it depends on the conditions and lifestyle, the remaining abilities, cooperation of other family members, and the role of rehabilitation team. Rehabilitation work includes medical, professional and social rehabilitation teams. The family is also defined as an essential member of the social rehabilitation team. The present study aimed to assess the quality of life of mothers of children with intellectual disabilities, as an important member of the social rehabilitation team. Methods: In this analytical and descriptive study, statistical population consisted of all Mothers of Mentally Retarded Children (MMRC) (educable, trainable and isolated), and Mothers of Children with Normal Intelligence (MCNI) in Shahr-e-Kord City, Iran. Total sample size was considered to be 306. For gathering data, the 36-Item Short Form Health Survey instrument, validated in Iran, and for analyzing the data 1-way ANOVA, linear regression and discriminant analysis were used. Results: In terms of all quality of life dimensions and total score, there was a significant difference between the two groups (P<0.001) and MCNI group scored higher compared to MMRC group. The greatest difference between the two groups was related to physical function (effect size=40.7%), and the least was related to limitations in usual role activities because of emotional problems (effect size=30.9%). Discussion: Mothers are an important mediator in providing rehabilitation services (secondary or tertiary prevention) to their children. Once their roles are neglected in the rehabilitation team work, the secondary and tertiary prevention activities for the disabled child will not be effective, and in the near future, mothers will be among the most vulnerable groups requiring rehabilitation services. Therefore, during the provision of secondary and tertiary prevention services for children, mothers’ health status should also be monitored for the purpose of primary prevention.